A note on two-weight inequalities for multiple Hardy-type operators - Alexander Meskhi (Journal of Function Spaces and Applications)
Necessary and sufficient conditions on a pair of weights guaranteeing two-weight estimates for the multiple Riemann-Liouville transforms are established provided that the weight on the right-hand side satisfies some additional conditions.